“Det var en prestation i dagens nu. Det får man tycka!” - Forssén, Olivia; Stridsman, Emma (2022)
During the 1930’s, it was common for female forestry cooks to start cook and clean in the remote logging cabins. The forestry cooks improved the standard for the forest workers when they cooked healthy food and cleaned. The overall aim of this study was to investigate the role of the forestry cooks had in forestry in the middle of the 20th century and how their work differed between two geographic regions: Tornedalen and Västernorrland/Jämtland. In the study we also wanted to analyze and get deeper understanding of how the forestry cooks experienced their time in the forest. We interviewed eleven women who have worked as forestry cooks during the 40’s and the 50’s, where five informants have worked in Tornedalen and six have worked in Västernorrland/Jämtland. By qualitative interviews with open questions, these women have told us about their time as cooks in the forest. As a background to forestry cooks, we read earlier literature about forestry cooks, moreover we did a literature study about our study areas. The forestry cooks in Tornedalen and Västernorrland/Jämtland had similar working days when they cooked and cleaned in the forest cabins and planned their cooking and purchase. The greatest difference between the areas was that the cooks in Tornedalen prepared food from reindeer meat, used less fish and vegetables compared to Västernorrland/Jämtland. Another interesting difference was that the celebration of Shrove Tuesday was more common in Västernorrland/Jämtland. The forestry cooks did crucial work for the timber industry in northern Sweden during an important period of time. They improved the food, health and social standards in remote logging cabins and thus increased the productivity in forestry. All of our informants enjoyed their time as forestry cooks and many of them received a greater self-confidence after their work as forestry cooks. Under 1930-talet var det vanligt att kockor började hjälpa till att laga mat och hushålla i skogsarbetarkojorna. Skogsarbetarkockorna förbättrade standarden för ...